2020
DOI: 10.18415/ijmmu.v7i9.1884
|View full text |Cite
|
Sign up to set email alerts
|

Student Development Zone: Higher Order Thinking Skills (Hots) in Critical Thinking Orientation

Abstract: Education is an important thing for humans to need because it functions to prepare human resources in the nation's development process. There are several characteristics in formal education, namely: having a clear curriculum, applying certain conditions for students and teaching staff must meet certain classifications. A person's ability to achieve success in life is determined by how much his ability to think in facing and solving life's problems. Someone who has the ability to think critically will always ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 5 publications
(5 reference statements)
0
13
0
3
Order By: Relevance
“…Based on the data, it can be concluded that the STEM-based digital module produced is both valid and feasible to use, and that it effectively raises the HOTS of future elementary school teachers. In the era of the 4.0 industrial revolution, HOTS is a critical skill (Arbia et al, 2020;Jaenudin et al, 2020). This is due to the fact that HOTS makes it easier for people to solve difficult problems and make wise decisions.…”
Section:  Results and Discussionmentioning
confidence: 99%
“…Based on the data, it can be concluded that the STEM-based digital module produced is both valid and feasible to use, and that it effectively raises the HOTS of future elementary school teachers. In the era of the 4.0 industrial revolution, HOTS is a critical skill (Arbia et al, 2020;Jaenudin et al, 2020). This is due to the fact that HOTS makes it easier for people to solve difficult problems and make wise decisions.…”
Section:  Results and Discussionmentioning
confidence: 99%
“…Tes diberikan pada tahap pretest dan posttest dimana terdiri dari dua buah soal uraian berbasis Higher Order Thinking Skills (HOTS) yang diberikan pada tahap pretest dan posttest. Hal ini dikarenakan berbasis penelitian terdahulu, soal berbasis HOTS dapat digunakan untuk mengukur tingkat kemampuan berpikir kritis siswa (Akatsuka, 2019;Feriyanto & Putri, 2020;Jaenudin et al, 2020).…”
Section: Teknik Pengumpulan Dataunclassified
“…Salah satu dampak diterapkannya HOTS adalah memaksimalkan kinerja dan mengurangi kelemahan. Hal ini dapat diistilahkan dengan siswa yang dilatih untuk berpikir secara HOTS akan berpengaruh terhadap kemampuan, kecepatan, dan efisiensi dalam pengambilan sebuah keputusan (Heong et al, 2011;Jaenudin, Chotimah, Farida, & Syarifuddin, 2020;Rahayu, Sopandi, Anggaeni, Tursinawati, & Septinaningrum, 2021). Namun demikian, berdasarkan fakta yang ditemukan di lapangan menunjukkan bahwa kemampuan HOTS pada siswa pada dalam taraf rendah.…”
Section: Pendahuluanunclassified